DESIGN OF DEVELOPMENT EDUCATION PROGRAM BASED OUTSIDE OF SCHOOL EDUCATION - WHENCHING ALI,; ABD. HAMID ISA,; ABDUL RAHMAT, (International Journal of Innovations in Engineering Research and Technology, 2021)
The most feasible or possible problem or need to be made a program is accompanied by the availability of resources, both human resources, infrastructure and facilities, as well as funding sources for implementation. In line with that, the role of the developer of the entrepreneurship education program is actually also as an ambassador for development, which includes the roles of catalysts, process assistants, solution providers, and source liaison (catalysts, process helper, solution giver, and sources linker), so if there are no resources available as needed, the entrepreneurship education program developer acts as a link between learning resources, so that a meeting between learning needs and learning resources is possible.